Pengaruh Profesionalisme Dan Time Budget Pressure Pada Kinerja Auditor Dengan Motivasi Auditor Sebagai Variabel Pemoderasi - Wikanadi, Made Irna; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This research was conducted at the BPKP Representative of Bali Province. The sample in this study were all auditors with a total auditor number of 74 people. The number of research samples used was 51 respondents, with a saturated sampling method. The data collection method used was using a questionnaire that was distributed directly to the auditors who worked in BPKP Representatives of Bali Province. The data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA). Based on the results of multiple linear regression analysis found that professionalism has a positive effect on auditor performance and time budget pressure has a negative effect on auditor performance. Based on the regression moderation results that auditor motivation increases the influence of professionalism and time budget pressure on auditor performance. Keywords : professionalism, time budget pressure, auditor motivation, auditor performance